Evaluation of Tear Functions in Patiens with Pteygium and Pinguecula - Aydemir, Orhan; Alinak, Azat; Guler, Mete; Turkcuoglu, Peykan; Turgut, Burak (Annals of Medical Research, 2021)
None
Keywords: Tear function tests, Pinguecula, Pterygium